Quality of Life and Its Determinants Among Diabetic Patients in A Rural Area of Gautam Buddha Nagar, Uttar Pradesh, India - Dewan, Sangeeta; Srivastava, Shalini; Mahajan, Harsh; Juneja, Khushboo (National Journal of Community Medicine, 2023)
Context: Diabetes has become the largest health emergencies of 21st century. The burden of diabetes is increasing globally especially in developing economies like India. In the recent years, Physician’s interest has turned to the concept of quality of life (QOL) as an important treatment goal and an important component of therapy in the management of diabetes. The study was aimed to compare the quality of life of adult diabetic subjects with healthy subjects and to assess the factors affecting the quality of life among diabetic subjects. Methodology: A Community based cross sectional study was conducted among 250 diabetic subjects and 50 healthy subjects more than 18 years of age, based on WHO-Quality of Life-BREF (WHO-QOL-BREF) questionnaire manual in the rural area of District Gautam Buddha Nagar from Jan 2021-June 2022. Data collected were entered and statistically analyzed using statistical software (SPSS-22) Results: Overall quality of life and general health score was significantly poor among diabetic subjects as compared to healthy subjects. Quality of life was significantly lower in diabetic subjects ≥ 60 years of age, illiterate subjects and in diabetic subjects with presence of comorbidity. Conclusions: Overall QOL was poor among diabetic subjects as compared to healthy subjects.